Development and characterization of Luliconazole Loaded Solid Lipid Nanoparticles for Topical Delivery - Muktai N. Rudrurkar,; Vishweshwar M. Dharashive,; Dr. Sameer Shafi,; Anis J. Kazi, (Asian Journal of Pharmaceutical Research and Development, 2024)
Superficial fungal infections in immunocompromised patients can lead to various disorders and complications. There is a critical need for new topical treatment options for these fungal infections. Luliconazole (LUZ) is a topical antifungal medicine used to treat fungal infections. This paper aims to develop a new topical gel incorporating Luliconazole SLN (LUZ-SLN). The study suggests that LUZ-SLN embedded in a gel could serve as an effective drug delivery system for topical antifungal treatments. Initial experiments were conducted to characterize the LUZ-SLN and compare it with the raw drug. The prepared gel was found to be homogeneous, safe for human use, and non-irritating. The nano-systems demonstrated a 5-fold enhancement in solubility, a s4-fold increase in dissolution velocity, greater skin retention, and improved antifungal activity. The LUZ-SLN gel showed the highest drug retention in different skin layers within 8 hours. Additionally, both LUZ-SLN and Control exhibited higher ZOI (Zone of Inhibition) values (93mm and 87mm, respectively) compared to marketed cream (83mm ). This suggests that the LUZ-SLN-loaded gel was more effective in combating the fungus. Therefore, the LUZ-SLN-loaded gel presents a new approach with improved activity and enhanced dermal delivery for drugs with poor aqueous solubility, compared to traditional drug-containing gel formulations.